The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1365-2524.2010.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity of daily living problems in older cancer survivors: a population-based controlled study

Abstract: The ability to perform activities of daily living (ADL) is a crucial factor for independent functioning and living at home. This population-based cross-sectional study examines ADL problems in older cancer survivors compared with an age-matched cancer-free control group. According to both The Cancer Registry of Norway and self-report, 911 individuals > or =70 years had invasive cancer among the participants of The Health Study of Nord-Trøndelag County (HUNT-2) 1995-7. Three age- and gender-matched cancer-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…Activity of daily living (ADL) problems were defined as tasks to be maintained every day and divided into personal (P-ADL) problems and instrumental (I-ADL) problems corresponding to suggested categorisation [25]. Cronbach's coefficient alpha was 0.85 and 0.82 for P-ADL and I-ADL problems, respectively.…”
Section: Variablesmentioning
confidence: 99%
“…Activity of daily living (ADL) problems were defined as tasks to be maintained every day and divided into personal (P-ADL) problems and instrumental (I-ADL) problems corresponding to suggested categorisation [25]. Cronbach's coefficient alpha was 0.85 and 0.82 for P-ADL and I-ADL problems, respectively.…”
Section: Variablesmentioning
confidence: 99%
“…The symptom combination of pain, fatigue, anxiety and depression puts a high burden on the people with cancer. The consequences can be reduced ability to cope with activities of daily living (Grov, Fossa, & Dahl, , ), which may lead to the need for help and support while living at home. People with cancer often face remarkable pain problems with varying origins, such as the disease itself and its treatment (Chang, Arnold, & Savarese, ; Dawn, ).…”
Section: Introductionmentioning
confidence: 99%
“…While all cancer survivors may experience long-term effects following the acute survivorship phase (National Cancer Institute [NCI], 2004), those with functional limitations resulting from pre-existing impairments may have special concerns related to their diagnosis and treatment. Previous research has shown that co-morbid health problems or disabling conditions can directly impact treatment, prognosis, and longer term outcomes for cancer survivors, including the ability to maintain health and carry out activities of daily living (Beck, Towsley, Caserta, Lindau, & Dudley, 2009; Gonzalez, Ferrante, Van Durme, Pal, & Roetzheim, 2001; Grov, Fossa, & Dahl, 2010; NCI, 2004; Piccirillo et al, 2003; Piccirillo, Tierney, Costas, Grove, & Spitznagel, 2004). Those with prior limitations in activities of daily living struggle to promote their health and prevent secondary disabling conditions under the best of circumstances (U.S.…”
mentioning
confidence: 99%